2021
DOI: 10.3354/esr01116
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities of wild-captured Kemp’s ridley (Lepidochelys kempii) and green sea turtles (Chelonia mydas)

Abstract: Conservation efforts for endangered sea turtle species, such as Kemp’s ridley turtles Lepidochelys kempii and green turtles Chelonia mydas, may benefit from information on the microbial communities that contribute to host health. Previous studies examining host-associated microbiomes of these species have been limited in geographic region, life stage, and/or health. Here, we characterized the microbiome of the oral cavity and cloaca from wild-captured Kemp’s ridley and green turtles off the west coast of Flori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Compared to wild healthy Kemp’s ridley turtles from the Gulf of Mexico, the oral microbiome of cold-stunned turtles at intake shared similar predominant bacterial families, including Flavobacteraceae and Rhodobacteraceae [ 64 ]. The cloacal samples, by contrast, were different between the healthy wild Kemp’s ridley turtles and the cold-stunned stranded turtles with no shared dominant families between the two groups [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to wild healthy Kemp’s ridley turtles from the Gulf of Mexico, the oral microbiome of cold-stunned turtles at intake shared similar predominant bacterial families, including Flavobacteraceae and Rhodobacteraceae [ 64 ]. The cloacal samples, by contrast, were different between the healthy wild Kemp’s ridley turtles and the cold-stunned stranded turtles with no shared dominant families between the two groups [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to wild healthy Kemp’s ridley turtles from the Gulf of Mexico, the oral microbiome of cold-stunned turtles at intake shared similar predominant bacterial families, including Flavobacteraceae and Rhodobacteraceae [ 64 ]. The cloacal samples, by contrast, were different between the healthy wild Kemp’s ridley turtles and the cold-stunned stranded turtles with no shared dominant families between the two groups [ 64 ]. Cardiobacteraceae, Flavobacteraceae, and Neisseriaceae were most prevalent in the wild healthy turtles, while Vibrionaceae, Arcobacteraceae, Shewanellaceae, and Rhodobacteraceae were prevalent from the intake cloacal samples of cold-stunned turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty wild caught green sea turtles were caught off the coast of Florida adjacent to the St. Martins Marsh Aquatic Preserve of Crystal River. Among all 20 samples the families Neisseriaceae and Arcobacteraceae were found to have the highest percent mean abundance (MA) at 29.2% and 14.7% respectively [56]. These findings are more comparable to samples obtained from stranded and hospitalized green sea turtles [32,38] and brings forth the question, what external factors may be affecting the cloacal microbiota?…”
Section: Keene Et Al Investigated Cloacal Samples From Green Andmentioning
confidence: 63%
“…In direct contrast to the two other studies on wild caught green sea turtles [38,51], McNally et al 2021 found an abundance of microbial families within the Proteobacteria phylum in wild caught green sea turtles [56]. Twenty wild caught green sea turtles were caught off the coast of Florida adjacent to the St. Martins Marsh Aquatic Preserve of Crystal River.…”
Section: Keene Et Al Investigated Cloacal Samples From Green Andmentioning
confidence: 88%
See 1 more Smart Citation